2015
DOI: 10.1007/s11548-015-1306-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delay on telesurgical performance: study on the robotic simulator dV-Trainer

Abstract: Gradually increasing latency has a growing impact on performances. Measurable deterioration of performance begins at 300 ms. Delays higher than 700 ms are difficult to manage especially in more complex tasks. Surgeons showed the potential to adapt to delay and may be trained to improve their telesurgical performance at lower-latency levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…From [47], it is visible that average latency of up to 100ms for transferring control signals to the ROV does not impair the ROV control algorithm. Extensive analysis of impact of delay on telesurgical performance was presented in [48]. It was concluded that deterioration of performance was noticeable for latencies above 300ms and that there was increase in errors during control for latencies greater than 500ms.…”
Section: Discussionmentioning
confidence: 99%
“…From [47], it is visible that average latency of up to 100ms for transferring control signals to the ROV does not impair the ROV control algorithm. Extensive analysis of impact of delay on telesurgical performance was presented in [48]. It was concluded that deterioration of performance was noticeable for latencies above 300ms and that there was increase in errors during control for latencies greater than 500ms.…”
Section: Discussionmentioning
confidence: 99%
“…It can be crucial in many cases, in particular for surgeries that require about a dozen of milliseconds, such as for the surgical precision and task completion during the future robotic-assisted remote telepresence surgery. For short terms, the obtained latency still satisfies the surgeons when it comes to human interaction with a remote expert, such as providing an advice or guidance during an ongoing surgery that do not require instantaneous reaction, however, in future work, it needs to be optimized and kept below 200 ms, as studied in [20].…”
Section: Resultsmentioning
confidence: 93%
“…Xu et al 31 claimed that the impact of latency on instrument manipulations was mild in the 0 to 200-ms range and that a less than 200-ms latency was ideal for telesurgery. Perez et al 32 reported a measurable deterioration in the performance beginning at a latency of 300 ms. Based on these results, our measured system latency is within a clinically acceptable range. As described earlier, the major contribution to the overall latency is from the Visionsense stereoscopic vision system, not the AR visualization itself.…”
Section: Discussionmentioning
confidence: 98%